Enhancing Junior High School Students’ School Well Being Through Parental Involvement in Education - Nurfajriyanti Rasyid; M. Ahkam Alwi; Astiti Tenriawaru Ahmad (Indonesian Journal of Educational Studies, 2025)
School well-being is a key indicator of students’ psychological adjustment and academic success. Early adolescents face increasing psychological pressure and complex academic demands, highlighting the crucial role of family support in maintaining their well-being at school. This study examined the influence of parental involvement on the school well-being of 150 junior high school students in Makassar and Gowa, Indonesia, using a quantitative correlational design. The instruments included the school well being schale and the Parental involvement schale, both balidated through content and reability testing. The result revealed a strong positive correlation between parental involvement and school well being (r=0,782, p<0,01). Simple linear regression analysis showed that parental involvement accounted for 61,2% of the variance in school well being. These findings underscore the essential role of parents in fostering students’ positive psychological experiences at school and emphasize the urgency of developing programs that strengthen parent-school partnerships.